2020
DOI: 10.7494/geom.2020.14.1.15
|View full text |Cite
|
Sign up to set email alerts
|

3D Technologies as the Future of Spatial Planning: the Example of Krakow

Abstract: The main goal of the paper is to make a general assessment of the application of 3D technologies in spatial planning. It was performed with the city of Krakow as the case study. The paper describes the outline of the spatial planning system in Poland and the planning conditions of Krakow. The data obtained from laser scanning for Krakow are also briefly characterized. The possibility of using these data for locating high-rise buildings in terms of the protection of Krakow's panorama and within two programs "IT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…In the opinion of the authors, drawing conclusions on air quality based on data obtained from sensors installed on measurement stations or remote sensing data as well as analyzing these data in reference to the zone (entire city) is The studies conducted by the authors indicate that only the detailed assessment of air quality based on geostatistical analyses accounting for the spatial structure of terrain and the variability of sources of pollution (dynamic of motor vehicle traffic) can give reliable information on the level of pollutions in the city. A similar view was expressed by [10,11,30]. The application of an integrated research method connecting advanced GIS technologies with the COPERT emissions calculator allows for a very detailed means of selecting areas in danger of carbon monoxide pollution and, thus, the effective selection of measures aimed at improving air quality.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…In the opinion of the authors, drawing conclusions on air quality based on data obtained from sensors installed on measurement stations or remote sensing data as well as analyzing these data in reference to the zone (entire city) is The studies conducted by the authors indicate that only the detailed assessment of air quality based on geostatistical analyses accounting for the spatial structure of terrain and the variability of sources of pollution (dynamic of motor vehicle traffic) can give reliable information on the level of pollutions in the city. A similar view was expressed by [10,11,30]. The application of an integrated research method connecting advanced GIS technologies with the COPERT emissions calculator allows for a very detailed means of selecting areas in danger of carbon monoxide pollution and, thus, the effective selection of measures aimed at improving air quality.…”
mentioning
confidence: 87%
“…Geostatistical tools solve various spatial problems [27][28][29] and allow for estimating the prediction error on the basis of the propagation of uncertainty. The potential for using 3D data to assess the quality of air was noticed by a research team from Krakow [30], who, based on data from the Integrated Spatial Data Monitoring System for the Improvement of Air Quality in Krakow, confirmed that geostatistical data can be successfully used for the assessment of air quality in a highly urbanized city. A modeling system comprising a road traffic model, a road transport emission model, and a computational fluid dynamics air quality model was used to assess air quality in a Portuguese City [11].…”
Section: Introductionmentioning
confidence: 99%
“…It is the second largest city in Poland in terms of population (about 780,000 inhabitants) and area (326.8 km 2 ). The city is an interesting research area for several reasons [47]. Firstly, it combines the historical buildings of three cities: the Old Town of Kraków (established in 1257), Kazimierz (14th century) and Podgórze (18th century).…”
Section: Research Areamentioning
confidence: 99%
“…The functionality of GMT enables its excellent operating of the cartographic commands which results in a high flexibility of writing a code and executing a script stepwise with a full control on the cartographic output. Many studies on mapping and spatial analysis are based on testing different GIS applied for various research questions, in which a large number of articles reported either the cartographic workflow and techniques of visualization (ČESNULEVIČIUS et al 2019;KESKIN et al 2019;LÓPEZ & BALBOA 2008;WOOD, 1993;LEMENKOVA, 2019aLEMENKOVA, , 2019bLEMENKOVA, , 2020aBIEDA et al 2020), present analysis of the cartographic visualization (e.g. OSTROWSKI et al 2019;MESENBUR, 2004;KEATES, 1996) or focused on the technical GIS applications (MACEACHREN, 1995;SLOCUM et al 1993;ROBINSON et al 1995).…”
Section: Introductionmentioning
confidence: 99%